Informal guiding. Enacting immediacy, informality and authenticity in Cuba - Simoni, V. (2019)
To better conceptualize the tourism encounter, scholars have highlighted the importance of mediators, notably tourist guides, in framing visitors’ experiences of a destination, encouraging to move beyond “hosts and guests”, “tourists and locals” binaries. The study of informal touristic encounters in Cuba helps problematize the identification of the tourist guide, highlighting the stakes of such categorization in a context of tightly regulated, state-led tourism development. Favouring a framing of tourist-Cuban interactions as genuine expressions of intimacy that escape the worker–customer binary, these encounters enact valued forms of informality, immediacy and authenticity. Their promise is to provide a “unique” glimpse into the “real” Cuba and the lives of “ordinary” Cubans, and to generate alternative possibilities for knowing and relating with the destination and its people.